(untitled) (Entrepreneurship Journal for Finance and Business, 2021)
This research aims to identify the role of banking governance in rationalizing financial decisions, and in order to achieve this, a hypothetical scheme was formulated from which the assumptions emerged which state the existence of correlations and influence between banking governance and the rationalization of financial decisions. Banking has a role in rationalizing financial decisions in banks, and the questionnaire form was used to collect data, and Rafidain Bank (in its Mosul and Bartella branches) was chosen as a community to implement the research, and its employees are a sample of 34 respondents. Data were analyzed and conclusions were drawn through the statistical program (SPSS). Ver 16), and many conclusions were reached, the most important of which is (that banking governance has an important role in rationalizing financial decisions in banks, and that the level of its approval and rationalization of financial decisions in the researched bank is roughly average) and based on the conclusions a set of proposals was proposed, the most important of which is (increase The interest of banks in banking governance because of its important role and clear influence in rationalizing financial decisions and thus contribute to making sound financial decisions to achieve goals Behold the strategy).